A role for the DtxR family of metalloregulators in gram‐positive pathogenesis. (22nd August 2013) - Merchant, A.T.; Spatafora, G.A.
Summary Given the central role of transition metal ions in a variety of biochemical processes, the colonization, survival, and proliferation of a bacterium within a host hinges upon its ability to overcome the metal ion deprivation that characterizes nutritional immunity. Metalloregulatory, or 'metal‐sensing' proteins have evolved in bacteria to mediate metal ion homeostasis by activating or repressing the expression of genes encoding metal ion transport systems upon binding their cognate metal ion. Yet increasing evidence in the literature supports an additional role for these metalloregulatory proteins in pathogenesis. Herein, we survey studies on the DtxR family of metalloregulators, namely DtxR (Cornyebacterium diphtheriae), SloR (Streptococcus mutans), MtsR (Streptococcus pyogenes), and MntR (Staphylococcus aureus) to describe how metalloregulation enables adaptive virulence gene expression within the mammalian host. This research has important implications for drug design, as the generation of hyper‐repressive metalloregulatory proteins may represent a mechanism by which to attenuate bacterial pathogenicity. The fact that metalloregulators are unique to prokaryotes makes these proteins especially attractive therapeutic targets.